Modern aspects of the use of calcium and vitamin D3 during pregnancy - O A Gromova; I Yu Torshin; N K Tetruashvili; I N Zakharova; T R Grishina (IP Berlin A.V., 2016)
The paper presents the results of systematic analysis of clinical effects of calcium important during pregnancy, including the appropriate fundamental molecular and physiological mechanisms of the clcium action. Clinical trials show that higher intakes of calcium and vitamin D3 in pregnancy help in the prevention of preeclampsia, normalization of the blood pressure and in the reduction of the risk of dental disease.